Financialisation and the slowdown of labour productivity in Portugal: A post-Keynesian approach - Diogo Correia; Ricardo Barradas (PSL Quarterly Review, 2021)
This paper conducts a time series econometric analysis in order to empirically evaluate the role of financialisation in the slowdown of labour productivity in Portugal during the period from 1980 to 2017. During that time, the Portuguese economy faced a financialisation phenomenon due to the European integration process and the corresponding imposition of a strong wave of privatisation, liberalisation and deregulation of the Portuguese financial system. At the same time, Portuguese labour productivity exhibited a sustained downward trend, which seems to contradict the well-entrenched mainstream hypothesis on the finance-productivity nexus. Based on the post-Keynesian literature, we identify four channels through which the phenomenon of financialisation has impaired labour productivity, namely weak economic performance, the fall in labour's share of income, the rise of inequality in personal income, and an intensification of the degree of financialisation. The paper finds that the main triggers for the slowdown of labour productivity in Portugal are the degree of financialisation and personal income inequality over the last decades.
Keywords: C22; E12; E24; E44; 330; Financialisation; Generalised Method of Moments; Labour Productivity; Portugal; Time Series